Insights into the immunomodulatory regulation of matrix metalloproteinase at the maternal-fetal interface during early pregnancy and pregnancy-related diseases - Jing, Mengyu; Chen, Xi; Qiu, Hongxia; He, Weihua; Zhou, Ying; Li, Dan; Wang, Dimin; Jiao, Yonghui; Liu, Aixia (Frontiers in Immunology, 2023)
Trophoblast immune cell interactions are central events in the immune microenvironment at the maternal-fetal interface. Their abnormalities are potential causes of various pregnancy complications, including pre-eclampsia and recurrent spontaneous abortion. Matrix metalloproteinase (MMP) is highly homologous, zinc(II)-containing metalloproteinase involved in altered uterine hemodynamics, closely associated with uterine vascular remodeling. However, the interactions between MMP and the immune microenvironment remain unclear. Here we discuss the key roles and potential interplay of MMP with the immune microenvironment in the embryo implantation process and pregnancy-related diseases, which may contribute to understanding the establishment and maintenance of normal pregnancy and providing new therapeutic strategies. Recent studies have shown that several tissue inhibitors of metalloproteinases (TIMPs) effectively prevent invasive vascular disease by modulating the activity of MMP. We summarize the main findings of these studies and suggest the possibility of TIMPs as emerging biomarkers and potential therapeutic targets for a range of complications induced by abnormalities in the immune microenvironment at the maternal-fetal interface. MMP and TIMPs are promising targets for developing new immunotherapies to treat pregnancy-related diseases caused by immune imbalance.